(untitled) (Portuguese Journal of Family Medicine and General Practice, 2004)
As family doctors we are asked regularly to testify about the ability of our clients to the most varied functions and activities. In the case of arrangements involving pressure variations, as in the case of skydiving and scuba diving, it is important to know that there is a substantially different pathophysiology from that of other sports, leading to a situation perfectly acceptable for a sports high competition can be an absolute contraindication for these procedures. In this article, we summarize the key features of these activities themselves, as well as the precautions to be taken in the evaluation of the users that want to practice. Because the pressure variations are more important in diving than in parachuting, dedicate ourselves to the first priority, making reference to our laws and what is accepted as good medical practice in the rest of Europe.